(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Improper disposal of unused and expired antibiotics has become a significant environmental and public health concern due to the release of active pharmaceutical residues into soil and water systems, contributing to antimicrobial resistance (AMR). The present study proposes the development of a Disposal-Activated Antibiotic Neutralizing Pouch, an innovative and eco-friendly approach for the safe disposal of leftover antibiotics at the household level. The proposed pouch is designed as a small biodegradable sachet attached to the medicine package and remains inactive during normal storage and use. After the medicine expires or treatment is discontinued, leftover tablets can be placed inside the pouch, followed by the addition of a small quantity of water to activate the neutralizing system. The pouch contains natural adsorbent and biodegradable materials such as activated bio char, bentonite clay, chitosan-based adsorbents, and, where feasible, oxidative enzymes such as laccase or peroxidase to adsorb or degrade antibiotic residues before disposal. The developed formulation will be evaluated for its physical properties, water activation time, adsorption efficiency, neutralization capacity, biodegradability, and environmental safety using appropriate analytical techniques. The proposed system is expected to significantly reduce the release of active antibiotic residues into the environment, thereby minimizing ecological contamination and helping to combat the spread of antimicrobial resistance. This simple, cost-effective, and user-friendly disposal technology has the potential to improve household pharmaceutical waste management and promote sustainable environmental protection while supporting responsible antibiotic stewardship.